DETERMINATION OF THE MECHANICAL PROPERTIES OF Al/MWCNT COMPOSITES OBTAINED WITH THE REINFORCEMENT OF CU-COATED MULTIWALL CARBON NANOTUBES (MWCNTs) - (:unkn) unknown (INST ZA KOVINSKE MATERIALE I IN TEHNOLOGIE, 2020)
In this study, Al/MWCNT composites were produced by milling copper-coated MWCNTs in small amounts (2.5-7.5%) with aluminum powders using the mechanical alloying method. Then, sintering was applied to the composite material. A phase analysis and microstructure investigations were performed on the as-sintered samples. A hardness test was conducted and tribological performances of the unreinforced and MWCNT-reinforced composites were examined at room temperature. Results showed that the hardness of the base-aluminum alloy was improved. The phase belonging to the MWCNTs was detected with an X-ray diffraction analysis. The wear rate generally decreased with the addition of MWCNTs in all test conditions. Sintering had a positive effect, enhancing the wear and hardness behaviour. Abrasive, adhesive, oxidative and thermal wear mechanisms were observed with a scanning electron microscope (SEM).
Keywords: powder metallurgy; MWCNT; mechanical behaviour; Cu coating; WEAR BEHAVIOR; ALUMINUM; FRICTION